The scientific literature on coralligenous habitat and fishing impacts - Silva, Serena; Grande, Umberto; Rendina, Francesco; Buonocore, Elvira; Guidato, Michele; Contegiacomo, Monica; Franzese, Pier Paolo (Ecological Questions, 2024)
Among marine habitats, the coralligenous represents one of the most important biodiversity hotspots, also playing an important role in the carbon cycle. Coralligenous is a biogenic habitat of the circalittoral zone formed by calcareous structures built by crustose coralline algae and other assemblages of calcifying organisms. Due to its structural complexity, it is also considered one of the most vulnerable marine habitats, very sensitive to environmental changes, such as climate change, and to other anthropogenic impacts such as fishing activities. Trawling is the most harmful fishing method that is causing the degradation of large areas of coralligenous reef concretions. Small-scale and sport fishing can also cause damage to the most sensitive organisms of the coralligenous habitat that can be damaged or removed by fishing gear, both during the fishing activity and in the case of the involuntary abandonment of stranded or damaged fishing nets, also known as “ghost nets”. In this study, the global scientific literature on coralligenous habitat was explored, with a particular focus on human impacts and fishing activities. The analysis was carried out using the VOSviewer software, generating network maps based on literature data retrieved from the Scopus database. The results show that the scientific literature is mainly concentrated in Italy, proving the important contribution provided by the Italian research on the topic. The results also highlight a research gap in the application of environmental accounting methods to quantify and value natural capital and ecosystem services associated to the coralligenous habitat, and their loss due to human impacts.